Supermarket refrigeration systems in cold-climate regions: a comprehensive review of waste heat recovery potential, compatibility with district heating network integration, and forward-looking free-cooling-enabled operation - Reza, Abu Muhammad Mustakim; Streckienė, Giedrė (International Conference “Environmental Engineering”, 2026)
Supermarkets are among the most refrigeration-intensive commercial buildings, converting a large share of electricity consumption into rejected heat at condensers or gas coolers. In cold climates, low ambient temperatures improve refrigeration efficiency and increase the value of recovered heat for space heating, positioning supermarkets as important distributed heat sources for district heating networks. This paper presents a comprehensive review of supermarket refrigeration systems, focusing on waste heat recovery potential, district heating integration, and interactions with free-cooling-enabled operation. A whole-building heat balance approach distinguishes internal heat gains that offset onsite heating demand from refrigeration-generated heat streams that are technically recoverable and scalable for external use. The methodology combines a structured narrative literature review with a conceptual bottom-up scaling framework, synthesizing peer-reviewed research, field measurements, techno-economic analyses, standards, policy frameworks, and industry case studies. Refrigeration electricity demand is linked to rejected heat using a coefficient-of-performance-based thermodynamic formulation, while heat usability is assessed according to temperature level, system architecture, and district heating network compatibility. Reviewed studies indicate that approximately 50–70% of total rejected heat can be recovered as usable heat, depending on supermarket envelope, internal gains, system configuration and network temperature levels. Evidence shows that supermarket refrigeration systems generate large, continuous, centrally accessible waste heat streams that often equal or exceed annual space heating demand. Modern carbon dioxide transcritical systems enable high-grade heat recovery in cold climates. Application to the Lithuanian supermarket stock indicates approximately 1.26 TWh per year, confirming supermarkets as a non-marginal urban heat source.